2011
DOI: 10.1021/ie200858y
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Silver Nanoparticles by Cacumen Platycladi Extract: Synthesis, Formation Mechanism, and Antibacterial Activity

Abstract: Biosynthesis of Ag nanoparticles (AgNPs) by Cacumen Platycladi extract was investigated. The AgNPs were characterized by ultravioletÀvisible absorption spectroscopy (UVÀvis), transmission electron microscopy (TEM), selected-area electron diffraction (SAED), and X-ray diffraction (XRD). The results showed that increasing the initial AgNO 3 concentration at 30 or 60 °C increased the mean size and widened the size distribution of the AgNPs leading to red shift and broadening of the Surface Plasmon Resonance absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(124 citation statements)
references
References 67 publications
3
120
1
Order By: Relevance
“…Christensen et al (2011) studied the biological synthesis of AgNPs using Murraya koenigii leaf extract and the effect of broth concentration on reduction mechanism and particle size. Huang et al (2011) reported that increasing the AgNO 3 concentration at 30 or 65°C increased the mean size and the size distribution of the AgNPs. Singhal et al (2011) reported that Ocimum sanctum leaf extract can reduce AgNO 3 into AgNPs within 8 min of reaction time.…”
Section: Factors Affecting the Size And Morphology Of Ag Nanoparticlesmentioning
confidence: 99%
“…Christensen et al (2011) studied the biological synthesis of AgNPs using Murraya koenigii leaf extract and the effect of broth concentration on reduction mechanism and particle size. Huang et al (2011) reported that increasing the AgNO 3 concentration at 30 or 65°C increased the mean size and the size distribution of the AgNPs. Singhal et al (2011) reported that Ocimum sanctum leaf extract can reduce AgNO 3 into AgNPs within 8 min of reaction time.…”
Section: Factors Affecting the Size And Morphology Of Ag Nanoparticlesmentioning
confidence: 99%
“…Briefly, AgNPs at 5, 0.5, and 0.05 μg/mL were used to prevent E. coli (ATCC 25922) and S. aureus (ATCC 25923) growth. Bacterial cultures at a concentration of 1.5 × 10 8 CFU/mL were inoculated with different concentrations of AgNPs [31]. After incubating the culture plates at 37 °C for 24 h, the bacterial growth inhibition zone was measured in millimeters [32].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Reducing sugars and flavonoids in the extract seemed to be mainly responsible for reduction of silver ions, and their reductive capability promoted at 90 °C, leading to formation of silver nanoparticles (18.4 ± 4.6 nm) with narrow size distribution. The produced nanoparticles had significant antibacterial activity against both gram negative and gram positive bacteria (E. coli and S. aureus) (Huang et al 2011). In case of Cinnamon zeylanicum, the bark extract could be used in biosynthesis of cubic and hexagonal silver nanocrystals (31-40 nm) (Sathishkumar et al 2009).…”
Section: Synthesis Of Silver Nanoparticles By Plantsmentioning
confidence: 99%